Cytogenetic laboratory management : chromosomal, FISH, and microarray-based best practices and procedures - Mahler Zneimer, Susan (Wiley Blackwell, 2017)
"This title will provide cytogenetic, FISH and microarray laboratory standard operating procedures (SOP's) and information on how to effectively write SOP's; validation plans and summaries; chemical, safety, quality control and quality assurance programs; and plans for effective use of reagents, instruments and equipment"--